Does Corporate Diversification Destroy Value? - Graham, John R.; Lemmon, Michael L.; Wolf, Jack G. (Journal of Finance, 2002)
ABSTRACT We analyze several hundred firms that expand via acquisition and/or increase their number of business segments. The combined market reaction to acquisition announcements is positive but acquiring firm excess values decline after the diversifying event. Much of the excess value reduction occurs because our sample firms acquire already discounted business units, and not because diversifying destroys value. This implies that the standard assumption that conglomerate divisions can be benchmarked to typical stand‐alone firms should be carefully reconsidered. We also show that excess value does not decline when firms increase their number of business segments because of pure reporting changes.